S100β Levels in CSF of Nonambulatory Dogs with Intervertebral Disk Disease Treated with Electroacupuncture. (29th December 2013) - Murata Hayashi, Ayne; Fonseca Pinto, Ana Carolina Brandão Campos; Cortopassi, Silvia Renata Gaido; Marvulle, Valdecir; Ruivo Maximino, Jessica; Chadi, Gerson; Matera, Julia Maria
Abstract : The aim of the study was to investigate S100 β levels in the cerebrospinal fluid of nonambulatory dogs with intervertebral disk disease treated with electroacupuncture: 10 dogs with thoracolumbar disk extrusion graded 3 to 5 (EA group) and 7 dogs without neurologic dysfunction (control group). All dogs regained ambulation. S100 β was detected by Western blot analysis where EA group dogs were evaluated at two time points (M1 = before EA and M2 = when the dogs return ambulation) and at one time point from control group. In EA group dogs M1-S100 β levels were significantly higher than in control group. EA group dogs were divided into subgroups A (n = 7 —early motor recovery;6.7 ± 7.8 days) and B (n = 3 —late motor recovery;76 ± 17.0 days). M1-S100 β levels were similar between subgroups A and B. However, M2-S100 β levels were significantly higher in subgroup B than in subgroup A. An elevated S100 β levels were observed in dogs with late motor recovery. S100 β may be associated with neuroplasticity following spinal cord injuries with intervertebral disk extrusion. Further studies with larger numbers of subjects and control group with affected dogs are necessary to investigate the relationship between neurotrophic factors and electroacupuncture stimulation.